Pericardial fat is a nutritionally regulated depot of brown adipose tissue - Ojha, Shalini (2015)
Introduction: Obesity and related cardio-metabolic complications have acquired global epidemic proportions. Suboptimal nutritional environment in early life induces adaptations in energy homeostasis, metabolism and adipose tissue development that may confer short-term survival advantages but are detrimental in later life, particularly if nutrient supply is restored.